A Review on New Coronavirus Mechanism of Action - Golsorkhi, Mohaddeseh; Ravanshad, Yalda; Azarfar, Anoush; Ravanshad, Sahar (Journal of Pediatric Nephrology, 2020)
The new coronavirus outbreak caused by the severe acute respiratory syndrome coronavirus2 (SARS-CoV2) has resulted in more than 126750 deaths worldwide so far and billions of expenses for the governments. SARS-CoV2, similar to SARS, was transmitted from bats and spread via human to human closed contacts. The virus uses its spike protein to bind to angiotensin-converting enzyme 2 receptors on target cells to replicate. Consequently, it spreads from infected cells to contaminate other cells. The body’s first response toward the virus is to activate the innate immune system, leading to the synthesis of inflammatory mediators. In the next step, the adaptive immune system appears where B lymphocytes produce antibodies specific for the virus, and CD8+ cells kill the infected cells directly. In this article, we try to explain the virus mechanism of action and immune response in detail. Although many questions remain unanswered, we expect this review could help in vaccine and treatment progression, Keywords: COVID-19; SARS-CoV2; Mechanism; Review.